1999
DOI: 10.1002/(sici)1098-2361(1999)18:6<565::aid-zoo10>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D metabolites 25(OH)D and 1,25(OH)2D and kidney function indices and the relationship to diet in Goeldi's monkeys (Callimico goeldii)

Abstract: keys, 3) although dietary vitamin D did not cause the renal problems, the renal dysfunction may have influenced the vitamin D metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…Free-ranging howler monkeys possessed circulating vitamin D metabolites above the levels for captive spider monkeys (another New World monkey), captive Cercopithecidae, great apes, and humans ( Table 2). The animals in this study had higher concentrations of both vitamin D metabolites compared to those reported for captive Callimico goeldii (2171.4, 25(OH)D and 14178.7, 1,25(OH) 2 D) [Crissey et al, 1999a]. However, renal dysfunction may have affected the values in that study.…”
Section: Vitamin Dcontrasting
confidence: 62%
See 1 more Smart Citation
“…Free-ranging howler monkeys possessed circulating vitamin D metabolites above the levels for captive spider monkeys (another New World monkey), captive Cercopithecidae, great apes, and humans ( Table 2). The animals in this study had higher concentrations of both vitamin D metabolites compared to those reported for captive Callimico goeldii (2171.4, 25(OH)D and 14178.7, 1,25(OH) 2 D) [Crissey et al, 1999a]. However, renal dysfunction may have affected the values in that study.…”
Section: Vitamin Dcontrasting
confidence: 62%
“…Total cholesterol, triacylglyceride, and LDL-cholesterol for this population of howlers were within the range for humans and most captive nonhuman primates, but lower than values reported for captive spider monkeys (Ateles geoffroyi), and higher than reported for captive Callitrichidae [Crissey et al, 1999a;Hainsey et al, 1993;Loeb and Quimby, 1989]. Howler HDL-cholesterol levels were near or within ranges for humans and nonhuman primates, but higher than for captive Callitrichidae (Table 2).…”
Section: Lipidsmentioning
confidence: 48%
“…Most New World primates have been reported to have extremely high levels of circulating vitamin D 3 metabolites in both the 25(OH)D 3 and 1,25(OH) 2 D 3 forms with levels two to 10 times higher than those found in Old World primates and humans ([Adams et al, ; Crissey et al, ; Gacad et al, ] with the exception of Callimico). Several species of New World primates have a high expression of competitive binding proteins intracellular that bind to the vitamin D metabolites and require elevated levels of both 1,25(OH) 2 D 3 for activation of cells and 25(OH)D 3 as the substrate for 1,25(OH) 2 D 3 production [Adams et al, ; Liberman et al, ; Teixeira et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Reported values of 25(OH)D 2&3 and 1,25(OH) 2 D 2&3 for nonhuman primates generally are higher than human values [Shinki et al, ]. Most New World primate levels reported are 2–10 fold higher than Old World monkeys (Adams et al []; but see Crissey et al [] for lower values in Callimico goeldii ) probably due to high expression of intracellular vitamin D binding proteins and concurrent high baseline levels of 1,25(OH) 2 D 3 . Additionally New World monkeys cannot utilize vitamin D 2 and rely solely on vitamin D 3 [Marx et al, ].…”
Section: Introductionmentioning
confidence: 99%